Barrier-free reverse-intersystem crossing in organic molecules by strong light-matter coupling - Yi Yu (Nature Portfolio, 2021)
Strong coupling of organic materials with optical cavities allows to manipulate the rate of energy transfer between their internal states. Here, the authors show a hybrid state of singlet character with energy lower than the triplet state, and a flow of energy from the triplet to the hybrid state.